IMPLEMENTATION OF THE 2023 ANNUAL MOTOR VEHICLE TAX FINES DISPENSATION POLICY AT THE ONE-ROOF SINGLE ADMINISTRATION SYSTEM (SAMSAT) BARRU - Rahmi Rais; Sri Hardiyanti Lukman (P3M Stia Al Gazali Barru and Meraja media, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal